2019
DOI: 10.5606/tr-ent.2019.51423
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vestibular system using c-VEMP and o-VEMP in patients with relapsing-remitting multiple sclerosis

Abstract: Objectives:This study aims to evaluate the role of vestibular evoked myogenic potentials (VEMPS; the cervical VEMP [cVEMP] and the ocular VEMP [oVEMP]) in the vestibular system in patients with relapsing-remitting multiple sclerosis (RRMS). Patients and Methods:Between December 2016 and December 2017, a total of 42 ears of 21 RRMS patients (8 males, 13 females; mean age 41 years; range, 25 to 57 years) and 42 ears of 21 healthy controls (7 males, 14 females; mean age 44 years; range, 38 to 62 years) were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In cVEMP testing of 42 ears of 21 relapsing-remitting multiple sclerosis (RRMS) patients, Tutar et al [17] found that the mean P1 and N1 latencies of the left ears of RRMS patients were significantly higher compared to the controls. There was no significant difference between patients and controls in terms of the P1-N1 interval or mean amplitude of the left ear (p>0.05).…”
Section: Comparison Of Cvemp and Ovemp In Ms And Controlsmentioning
confidence: 99%
See 2 more Smart Citations
“…In cVEMP testing of 42 ears of 21 relapsing-remitting multiple sclerosis (RRMS) patients, Tutar et al [17] found that the mean P1 and N1 latencies of the left ears of RRMS patients were significantly higher compared to the controls. There was no significant difference between patients and controls in terms of the P1-N1 interval or mean amplitude of the left ear (p>0.05).…”
Section: Comparison Of Cvemp and Ovemp In Ms And Controlsmentioning
confidence: 99%
“…For oVEMP testing, Tutar et al [17] found that 8 RRMS patients (19%) had no response in the oVEMP test of the right ear (n = 4) and left ear (n = 4). There was no significant difference in P1 or N1 latencies or the P1-N1 interval, amplitude of right ears, or amplitude asymmetry ratio between the patients and controls (p>0.05 for all).…”
Section: Comparison Of Cvemp and Ovemp In Ms And Controlsmentioning
confidence: 99%
See 1 more Smart Citation